Rethinking altitude and child growth: evidence from a multi-altitude study in Tibet - Shao, Shubin; Ma, Xiaowei; Wangyai, Dawa; Wang, Jian; Agudamu,; Zhang, Yang (Frontiers in Nutrition, 2025)
ObjectiveHigh-altitude environments have long been linked to growth deficits in children, often attributed to chronic hypoxia. Yet, emerging evidence from better-resourced highland communities suggests that socioeconomic and infrastructural factors may be equally or more influential. This study evaluated growth and nutritional disparities among Tibetan children across altitudes and assess the continued relevance of the altitude-growth paradigm.MethodsA repeated cross-sectional study in 2019 and 2024 surveyed 28 schools in Qamdo, Tibet (3200–4,500 m), collecting anthropometric and lung function data from 8,230 children (47.4% boys) aged 6–17 years. Regional growth standards were updated using GAMLSS. Logistic regression examined associations of age, sex, and altitude with stunting, underweight, and overweight, using girls and ~3,200 m as the reference groups.ResultsIn 2024, adolescent height approached national norms, with marked gains since 2019. Stunting (12.3%) and underweight (9.2%) remained prevalent. Compared to ~3,200 m, children at ~3,600 m had higher odds of stunting (OR 6.10, 95% CI 4.94–7.58) and underweight (OR 9.03, 95% CI 7.05–11.63), while >4,000 m showed smaller increases (stunting OR 3.43; underweight OR 4.63). Boys had greater odds of stunting (OR 1.16, 95% CI 1.02–1.33) and underweight (OR 1.34, 95% CI 1.15–1.56) than girls. Body mass index rose in 2024 but remained below national averages; body fat was consistently lower.ConclusionNon-linear altitude effects and catch-up growth under improved conditions suggest altitude is an indirect risk factor mediated by modifiable socioeconomic constraints, challenging deterministic altitude-growth models and supporting targeted nutrition and infrastructure policies.